The Application of Critical Literacy Through Okky Madasari’s Short Story “Yang Bertahan dan Binasa Perlahan” in Indonesian Language Learning - Lamri, Lamri; Sulastri, Sri Yunia (Salingka, 2025)
This research is motivated by the discrepancy between the idealism of the Merdeka Curriculum, which emphasizes critical thinking skills, and the instructional reality of literature learning, which tends to remain stagnant within a mechanistic-atomistic approach. The purpose of this study is to examine the effectiveness of Okky Madasari's short story “Yang Bertahan dan Binasa Perlahan” as a pedagogical instrument to escalate critical thinking skills from the perspective of critical literacy. The method employed is descriptive qualitative with a content analysis design, synergized with the Reader-Response approach and Facione’s critical thinking indicators. The research subjects consisted of 14 eleventh-grade students of SMA IT Al-Huda, selected through a purposive sampling technique. Data were gathered through participatory observation, essay tests, and documentation of discussion transcripts. The results indicate a significant escalation in cognitive participation, rising from 45% in the pre-reading stage to 90% in the post-reading stage. The findings reveal that the short story successfully triggered intellectual dissonance, compelling students to engage in a deconstruction of authority hegemony, multidimensional ethical evaluations, and sociological inferences regarding the phenomenon of marginalization. This study proposes the critical transactional hermeneutics model as a theoretical synthesis to reconstruct literature learning from mere knowledge transmission into a transformative arena for intellectual dialectics.Penelitian ini dilatarbelakangi oleh adanya diskrepansi antara idealisme Kurikulum Merdeka yang menekankan keterampilan berpikir kritis dengan realitas instruksional pembelajaran sastra yang cenderung stagnan pada pendekatan mekanistik atomistik. Tujuan penelitian ini adalah untuk menguji efektivitas cerpen “Yang Bertahan dan Binasa Perlahan” karya Okky Madasari sebagai instrumen pedagogis untuk mengeskalasi keterampilan berpikir kritis siswa melalui perspektif literasi kritis. Metode yang digunakan adalah deskriptif kualitatif dengan desain analisis isi, yang disinergikan dengan pendekatan Reader-Response dan indikator berpikir kritis Facione. Subjek penelitian adalah 14 siswa kelas 11 SMA IT Al-Huda yang dipilih melalui teknik purposive sampling. Data dihimpun melalui observasi partisipatif, tes esai, dan dokumentasi transkrip diskusi. Hasil penelitian menunjukkan adanya eskalasi partisipasi kognitif yang signifikan, dari 45% pada tahap pra-baca menjadi 90% pada tahap pascabaca. Temuan penelitian mengungkapkan bahwa teks cerpen berhasil memicu disonansi intelektual yang memaksa siswa melakukan dekonstruksi terhadap hegemoni otoritas, evaluasi etis multidimensional, dan inferensi sosiologis terhadap fenomena marginalisasi. Penelitian ini mengajukan model hermeneutika transaksional kritis sebagai sintesis teoretis untuk merekonstruksi pembelajaran sastra dari transmisi pengetahuan menjadi arena dialektika intelektual yang transformatif.